Is China market socialist? Comparing Western theory to Eastern practice. Issue 1 (2nd January 2022) - Yunker, James A.
ABSTRACT: The question of whether the contemporary Chinese economy is more accurately characterized as market socialist or market capitalist depends to some extent on semantic issues pertaining to the meaning of terms such as capitalism, socialism, and the market. Adding to these complications is the fact that there are several market socialist plans, quite different in their specifics, extant in the systems literature produced by Western economists. The present contribution attempts to shed a more focused light on this question by comparing the contemporary Chinese economy to a specific plan of market socialism known as 'pragmatic market socialism.' While obviously not a perfect match, there appears to be sufficient overlap for the Chinese economy to be considered a reasonable approximation to pragmatic market socialism.